Al-Kalam Al-Insya’I wa Ma’anihi fi Surati Al-Shaffat - Muhimmatul Musyayyadah (Journal of Arabic Literature (JaLi), 2020)
Balāghah is a science that studies the style of language in a text or expression. Some kinds balāghah studies are ‘ilmu bayān, ‘ilmu ma’ānī, and ‘ilmu badī’. In this study, the researcher studied surah al-Sāffāt by using the study of balāghah ‘ilmu ma’ānī namely Kalām Inshā’ī. Kalām Inshā’ī  is an expression that does not show truth or lies. Kalām Inshā’ī divided to two parts, that is kalām inshā’ī ṭalabī dan kalām inshā’ī ghairu ṭalabī. Through a qualitative descriptive approach, the present study reveals that there are 47 sentences consisting of kalām inshā’ī including: 16 amr (imperatives), 22 istifhām (interrogative), 2 tamannī, 4 nidā’, 2 qasm, and 1 madh.